Colégio Maria Auxiliadora de Coxipó da Ponte : entre o ensino religioso e o ensino elementar (1898-1917) - Silva, Roberto Costa (2022)
The research analyzes the relationship between religious education and elementary education offered by Colégio Maria Auxiliadora de Coxipó da Ponte – Cuiabá/MT. It was an institution that operated in a boarding and day care regime aimed at female children. The time frame is located from 1898, the year of its foundation, ending the research in 1917, since from that year the sisters became responsible for the direction of the Public School of Coxipó da Ponte. In view of this, the following problem was presented: how did the Colégio Maria Auxiliadora de Coxipó da Ponte work during this period, given that it integrated the educational practices of religious education and elementary education? That said, it was outlined as a general objective: to understand how the relationship between religious education and elementary education offered by Colégio Maria Auxiliadora de Coxipó da Ponte took place through an analysis of educational practices. The specific ones, on the other hand, are: Outline the trajectory of the Daughters of Maria Auxiliadora in Mato Grosso and in Coxipó da Ponte – Cuiabá. Apprehend the educational process in the region of Coxipó da Ponte; Bring, to the light of the History of School Institutions, the foundation of Colégio Maria Auxiliadora de Coxipó da Ponte; To analyze the educational practices of Colégio das Irmãs; and, to explore the way in which the institution's religious education and elementary education were administratively organized. The methodology is based on bibliographic and documental research, using Michel De Certeau's Operation Historiographic (1999), articulating the examination around an institution, seeking to understand its social place, the relationship between existing practices, culminating in the writing of its history through the analysis of the consulted sources. The theoretical bases are inserted in the field of History of Education, in order to understand the history of school institutions. Thus, it is based especially on the contributions of the respective authors: Sacristán (1999), Schueler (1999), Magalhães (2004), Nosella and Buffa (2009), Boto (2010), Sá (2007), Azzi (1982; 1999 ; 2002), Castro (2014), Francisco (2010) Duroure (1977). By way of conclusion, it is noted that the educational practices of the aforementioned college focused mainly on the activities of the Festive Festive Oratory for women, which, in turn, synthesize the religious and educational action of the Daughters of Maria Auxiliadora in Coxipó da Ponte, whose basis of support is found in the foundations of Don Bosco's Preventive System.